Peer Pressure and Discipline Management in the Nigerian Army: A Study of 8 Division, Sokoto State - Lazarus, Meshack; Fadahunsi, John A.; Agboaye, Peter David (Darul Yasin Al Sys, 2025)
This study examined peer pressure and discipline management in the Nigerian Army, focusing on the 8 Division in Sokoto State. It specifically investigated the effects of peer conformity, peer coercion, and peer communication on indiscipline among soldiers in the 8 Division, Nigerian Army, Sokoto State. A cross-sectional research design was adopted, with a sample size of 372 respondents determined using the Taro Yamane formula. Data were collected through structured questionnaires and oral interviews. The research questions were analysed using descriptive statistics such as the mean, while the hypotheses were tested using analysis of variance (ANOVA). The results showed that peer conformity, peer coercion, and peer communication play a significant role in fostering indiscipline within the Division. The study concludes that interpersonal relationships among soldiers are critical in determining their behaviour and compliance with military requirements. It recommends that military leadership embrace systematic mentorship programmes, develop efficient communication strategies, and establish effective reporting systems to minimise the adverse effects of peer pressure and enhance the level of discipline within the force.